Diagnostic Utility of Conventional Radiography in Head Injury - Chawla, Hitesh (J Clin Diagn Res, 2015)
BACKGROUND: Head injury is the frequent cause of morbidity and mortality and frequently encountered in emergency department. Radiological examination of the skull is an indispensable part in the management of patients suffering from head trauma. AIM: To determine the accuracy of X-ray in detecting skull fractures, comparing the same with autopsy and CT evaluation. MATERIALS AND METHODS: The medico-legal cases that died of traumatic head injury and brought for autopsy over a period of two years were included in the study. Only those cases were selected who had underwent both X-ray and CT evaluation prior to death. RESULTS: When compared with autopsy, X-ray missed 19.1% of fractures while 11.9% fractures missed in contrast to CT scan. CONCLUSION: Skull X-ray is of little benefit when a CT scan is obtained. It has no added advantage over CT scan. Whenever there is facility of CT scan is available, the patient of head injury should not underwent X-ray as it can only delay the diagnosis of an associated intracranial injury and exposes the already traumatised patient to harmful radiations.